Augmented Reality in Maintenance Training for Military Equipment. (October 2020) - Wang, Wei; Lei, Songgui; Liu, Haiping; Li, Taojin; Qu, Jue; Qiu, Ang
Abstract: After more than 20 years of development, augmented reality technology has shown a strong development momentum, successfully applied in civil and military fields. And augmented reality maintenance system is one of the most typical application. This paper introduces the present situation of augmented reality maintenance system, illustrates the structure of a typical system, discuss key technologies of augmented reality maintenance, and investigates the insufficiencies of it in military equipment maintenance according to the contemporary condition. Eventually, this paper indicates the potential development tendency of the augmented reality military equipment maintenance system in the future.